Strategic Management of Islamic Banking in Indonesia to Increase Market Share - Muhammad Ali Imran Caniago (Business Finance Analyst Co., 2023)
Indonesia is a country with the largest Muslim population in the world. The large Muslim population has not been able to make Indonesia the center of the world's sharia economy. One component of the Islamic economy in Indonesia is Islamic banking. The market share of Islamic banking in Indonesia is still very small, so the competition for market share in national banking is still won by conventional banks. This study aims to identify the market share of Islamic banking in Indonesia and strategies for developing and increasing the market share of Islamic banking to contribute to the national economy and development. The method used in this study is a qualitative method with a descriptive analysis approach. Data is collected through library research. The results of the study show that several strategic issues impede the growth of Islamic banking in Indonesia, namely: Islamic banks do not yet have a significant business model or product differentiation, Islamic bank literacy and inclusion indexes are still low, Islamic banks are still only focused on business objectives, The quantity and quality of Islamic Bank human resources are not optimal, and information technology is not yet sufficient. Knowing these strategic issues, three strategies are formulated in the development of Islamic banking: Strengthening Islamic Banking Identity, Synergy of the Islamic Economic Ecosystem, and Strengthening Licensing, Regulation, and Supervision.